Disrupting Intergenerational Maternal Maltreatment in Middle Childhood: Therapeutic Objectives and Clinical Translation - Amos, Jackie; Segal, Leonie (Frontiers in Psychiatry, 2018)
Background Child Maltreatment is a concerning worldwide problem. The population of distressed mothers with their highly disturbed children, in middle-childhood, often present to child and adolescent mental health services. Finding effective therapies for this population has proved elusive. This led the authors to undertake a theory-driven research program to better understand intergenerational child maltreatment from a clinical perspective, in order to determine how best to treat he entrenched distressing and destructive behaviours. Methods The model of the mechanisms of intergenerational maternal maltreatment is briefly described from which the objectives of therapy and associated principles of any effective treatment for these mothers and children are derived. A clinical model for achieving the therapeutic objectives is then elucidated. Findings Core objectives of therapy are; first to support the mother and child to develop differentiated senses of self and, second to disrupt a relationship style built on a competitive dominance and submission hierarchy, replacing it with a hedonic (cooperative and compassionate relationship style). This requires a deep healing of the mother and child’s trauma histories. A clinical operationalisation of these objectives, through a novel dyadic psychotherapeutic protocol, Parallel Parent and Child Therapy is described, which addresses the therapeutic objectives while attending to the safety of mother and child. Interpretation This research contributes to a better understanding of the components of effective treatment in what is a notoriously hard to treat population. It also illustrates the value of clinically informed theory development in understanding and refining treatment strategies for highly distressed and distressing populations.